2021
DOI: 10.3390/jpm11080712
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels in Asymptomatic Children and Adolescents with Atopy during the COVID-19 Era

Abstract: This study assessed vitamin D status in asymptomatic children and adolescents in Greece, with and without atopy, and possible changes during the coronavirus disease 2019 (COVID-19) pandemic. Serum levels of 25-hydroxy-vitamin D (25(OH)D) and total immunoglobulin E (IgE), and eosinophil count were measured in 340 asymptomatic children and adolescents (155 males, 185 females), mean age 8.6 ± 4.6 years, recruited over a period of 24 months (February 2019–January 2021). Atopy, defined by high level of IgE for age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Also, the median vit D level was higher in the children with a single episode of wheezing than in the control group. This could be explained by the fact that the control group consisted of older children, and in winter the serum level of vit D is reported to be lower in older children [35], as confirmed by the authors in previous studies [36,37]. In our study, significantly lower levels of vit D were found in children with recurrent wheezing than in either of those with a single episode, or in the control group, only at baseline evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…Also, the median vit D level was higher in the children with a single episode of wheezing than in the control group. This could be explained by the fact that the control group consisted of older children, and in winter the serum level of vit D is reported to be lower in older children [35], as confirmed by the authors in previous studies [36,37]. In our study, significantly lower levels of vit D were found in children with recurrent wheezing than in either of those with a single episode, or in the control group, only at baseline evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…As illustrated in Figure 1 , a total of 748 studies were identified through the initial searches in the above-mentioned databases; 317 were excluded due duplication among various databases and 256 papers were excluded by browsing the titles or abstracts. After retrieving 33 full-length manuscripts, 5 studies [ 12 , 13 , 20 22 ] were included into the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (4/5) were retrospective studies. Three studies [ 12 , 20 , 21 ] focused on people age 1–18 years and 2 on infants [ 13 , 22 ]. Nearly half of the study population were males.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D supplementation in pregnant women was shown to be associated with a lower rate of detection of specific IgE to food antigens in their children at the age of five years [ 26 ]. Sufficiency of Vitamin D appears to exert a protective role in the development of atopy and allergic diseases [ 27 , 28 ]. The Ω-3 fatty acids are a family of biologically active unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%